The Influence of Personality Traits and University Green Entrepreneurial Support on Students Green Entrepreneurial Intentions - Susana Avila Dude; Heni Mulyani (Economics Education Department Universitas Negeri Semarang, 2024)
This quantitative study seeks to explore the influence of personal traits and university support for green entrepreneurial intentions, while also considering gender as a control variable. The research population comprises 244 students, with a sample size of 152 students enrolled in economic education at the University of Education Indonesia. The theory used is the Theory of Reasoned Action (TRA). Data collection using a questionnaire. Data analysis techniques with structural equation modeling (SEM) with Smart PLS 3. The results of this study indicate that personal traits and university green entrepreneurial intention support have a positive and significant influence on green entrepreneurial intention. In addition, it was found that there is no difference in green entrepreneurial intention from the aspect of gender. It is suggested that it involves developing educational programs to form personal traits and strengthening university support, with industry collaboration for an environmentally sound environment. PLS was chosen as the analysis method because it is suitable for small sample sizes, model complexity, focus on prediction, and consideration of control variables such as gender. It is expected to provide an in-depth understanding of the factors that influence green entrepreneurial intention among university students.